Towards autonomy, self-organisation and learning in holonic manufacturing - Leitão, Paulo (2010)
This paper intends to discuss self-organisation and learning capabilities in autonomous and cooperative holons that are part of a holonic manufacturing control system. These capabilities will support the dynamic adaptation of the manufacturing control to the manufacturing evolution and emergency, specially the agile reaction to unexpected disturbances.